A biblical understanding of pain : its reasons and realities - Timmerman, John (Eugene, Oregon : Cascade Books, 2013)
In A Biblical Understanding of Pain: Its Reasons and Realities, John Timmerman examines six different sources of pain, each with its own chapter of description and biblical response. These include physical pain, the pain of mental illness, spiritual pain, emotional pain, the pain of the Prodigal, and the pain of memories. Additional chapters explore the sources of pain, the denial of pain, and the question of God's omnipotence and why he doesn't just remove pain. Rather than setting forth sets of rules governing our response to pain, Professor Timmerman narrates actual life events and examples, and then examines biblical responses to these. The result is a study that feels lived in.
Includes bibliographical references (pages 117-118).
Print version record.
Keywords: Suffering -- Religious aspects -- Christianity; Theodicy; Consolation; Consolation; Suffering -- Religious aspects -- Christianity; Theodicy; BODY, MIND & SPIRIT / Inspiration & Personal Growth; BODY, MIND & SPIRIT / Spirituality / General; RELIGION / Christianity / General; RELIGION / Devotional; RELIGION / Spirituality; Electronic books